THE EFFECT OF BABY MASSAGE WITH LAVENDER OIL ON QUALITY OF BABY SLEEP (AGE 6-12 MONTHS) IN MARUKANGAN VILLAGE, SANDARAN DISTRICT EAST KUTAI REGENCY - Adinda Dewi Utari; Chandra Sulistyorini; Eka Frenty Hadiningsih; Sucita Tripertiwi (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Background: Sleep is a basic need of living things that is important for physical, emotional recovery, and strengthening the body. However, 33% of babies in the world are reported to experience sleep disorders that can affect their cognitive and physical development. One of the non-pharmacological interventions used to improve the quality of infant sleep is baby massage using lavender oil. Objective: This study aims to determine the effect of baby massage with lavender oil on improving the quality of sleep of infants aged 6-12 months in Marukangan Village, Sandaran District, East Kutai. Method: Quantitative research with a quasi-experimental research method using a pre-test and post-test with control group design, sampling using a purposive sampling method with a sample size of 52 infants divided into intervention and control groups. The intervention group was given massage therapy using lavender oil for 45 minutes, while the control group did not receive similar treatment. Data were analyzed using the Wilcoxon test. Results: The results showed a significant increase in the quality of infant sleep in the intervention group, infants experienced good sleep quality after being given therapy, namely with a p-value of 0.003 (p-value <0.05). In contrast, the control group showed a lower increase. This proves that baby massage with lavender oil is effective in improving the quality of baby sleep. Conclusion: Baby massage with lavender oil can be an effective complementary intervention to improve the quality of baby sleep. It is expected that this method can be applied by midwives and parents as a non-pharmacological solution to overcome baby sleep disorders.